Class Management Factors in Serat Wirid Hidayat Jati - Nuswanto, Eko; Eliyanto, Eliyanto; Adib, Shohibul; Mahfudz, Ali; Fauziah, Muna (Asian Journal of Applied Education (AJAE), 2025)
This research is motivated by the trend of revitalization of educational concepts in Indonesia which are derived from the noble philosophy of the nation's culture. Thus, this study intends to conduct a study on classroom management factors based on Serat Wirid Hidayat Jati. This study uses a literature study approach. The researcher acts as the main instrument. Data collection techniques are carried out by collecting documents and analyzing them by classifying, systematizing, and formulating according to the main problem. The results of the study indicate that the factors that influence the implementation of classroom management according to Serat Wirid Hidayat Jati include classroom dynamics, seating arrangements, learning time arrangements, selection of learning locations, temperature settings, lighting, and air and water circulation. Classroom management needs to be adjusted to the characteristics of the objectives, materials and levels of mental maturity to become an alternative to classroom management at the elementary and secondary education levels in Indonesia, which mostly use conventional class models.